Low serum IgA and airway injury in World Trade Center-exposed firefighters: a 17-year longitudinal study. Issue 12 (14th October 2019) - Putman, Barbara; Lahousse, Lies; Zeig-Owens, Rachel; Singh, Ankura; Hall, Charles B; Liu, Yang; Schwartz, Theresa; Goldfarb, David; Webber, Mayris P; Prezant, David J; Weiden, Michael D
Abstract : Serum IgA ≤70 mg/dL (low IgA) is associated with exacerbations of chronic obstructive pulmonary disease. The association of low IgA with longitudinal lung function is poorly defined. This study included 917 World Trade Center (WTC)-exposed firefighters with longitudinal spirometry measured between September 2001 and September 2018 and IgA measured between October 2001 and March 2002. Low IgA, compared with IgA >70 mg/dL, was associated with lower forced expiratory volume in 1 s (FEV1 ) % predicted in the year following 11 September 2001 (94.1% vs 98.6%, p<0.001), increased risk of FEV1 /FVC <0.70 (HR 3.8, 95% CI 1.6 to 8.8) and increased antibiotic treatment (22.5/100 vs 11.6/100 person-years, p=0.002). Following WTC exposure, early IgA ≤70 mg/dL was associated with worse lung function and increased antibiotic treatment.